On k-tree Containment Graphs of Paths in a Tree - Alcón, Liliana Graciela (2020)
A k-tree is either a complete graph on k vertices or a graph that contains a vertex whose neighborhood induces a complete graph on k vertices and whose removal results in a k-tree. If the comparability graph of a poset P is a k-tree, we say that P is a k-tree poset. In the present work, we study and characterize by forbidden subposets the k-tree posets that admit a containment model mapping vertices into paths of a tree (CPT k-tree posets). Furthermore, we characterize the dually-CPT and strong-CPT k-tree posets and their comparability graphs. The characterizations lead to efficient recognition algorithms for the respective classes.